The synthesis, photophysical and dielectric properties of ball-type dinuclear zinc phthalocyanine - Canlica, Mevlude; Altindal, Ahmet; Nyokong, Tebello (WORLD SCI PUBL CO INC, 2012)
The synthesis of ball-type dinuclear Zn(II) phthalocyanine containing four 4,4'-(9H-fluorene-9,9-diyl)diphenol substituents at the non-peripheral position is presented. The structure of the synthesized compound was characterized using elemental analyzes, and UV-vis, FT-IR, H-1 NMR and mass spectroscopies. The Phi(F) value was 0.16 and Phi(T) value was 0.72. The complex showed reasonably long triplet lifetimes with tau(T) 7210 mu s in DMSO. The frequency and temperature dependence of the dielectric properties of ZnPc were also investigated in the frequency range of 40-10(5) Hz and in the temperature range of 300-440 degrees K. It has been observed that both dielectric constant epsilon' and dielectric loss epsilon'' decrease with the rise in frequency as they increase with the rise in temperature. The decrease in epsilon' with increasing frequency is attributed to the fact that as the frequency increases, the polarizability contribution from orientation sources decreases and finally disappears.
Keywords: Zn ball-type phthalocyanine; photodynamic therapy; non-peripheral phthalocyanine; triplet quantum yield; dielectric properties; 1,2-BIS(3,4-DICYANOPHENOXYMETHYL)BENZENE; Chemistry